Diabetes treatment and control using lifestyle intervention in outpatient setting: Case Series and Update: Tratamiento y control de la diabetes con intervención de estilo de vida en pacientes ambulatorios: Serie de Casos y Actualización - Valencia Leal, Amin A. (2021)
The prevalence of diabetes demands the identification of more efficient long-term methods to achieve good patient control. This paper reports the progress of 4 patients diagnosed with previously poorly controlled diabetes and prediabetes with comorbidities that were attended in an outpatient clinic, they received orientation regarding lifestyle change and were instructed to increase consumption of dietary fiber and physical activity. Body composition and biochemical markers were followed and changes were reported. In a 5 month period Patient 1 achieved criterion for controlled diabetes and was able to suspend oral hypoglycemic agents, reducing his body weight by 10%. Within a 8 week period Patient 2 experienced a 50% decrease of HOMA IR and was able to achieve criteria of controlled diabetes. Furthermore a 3 kg increase in lean body mass and a 4 kg body weight decrease were documented. These findings were accompanied by a 23% and 38% decrease in total cholesterol and triglycerides respectively. Patient 3 achieved criteria for type 2 diabetes remission within a 18 month time span(Inicial HBA1C 11.4% Final HBA1C 5.3). Patient 4 progressed to remission of prediabetes and a decrease of 5.9% in total body weight in a 3 month period.